Prospects and practices of enhancing students’ linguistic giftedness: the Kazakhstani experience (Philology, 2026)
The article discusses a small-scale experiment to examine the implementation of a strategic linguistic giftedness model with 12 pupils who have been chosen from a range of schools for gifted students over a period of 12 weeks. The impact of this experimental study is to provide learning activities that cater to all gifted students’ needs in the classroom and stimulate their linguistic giftedness and foreign language learning.This article is an attempt to make an experimental analysis of some problems associated with enhancing linguistically gifted students in their learning of English. In this respect, the results can assist teachers and practitioners in the effective organization of the educational process; but most of all, the study is addressed to foreign language teachers who are responsible for the selection of English teaching strategies that build the methodically calibrated educational process. This article also presents a linguistic giftedness curriculum which consists of 12 separate curriculum blocks with a complex of extra-curricular activities for linguistically gifted students.
Keywords: linguistic giftedness; foreign language aptitude